Analisis Faktor yang Mempengaruhi Keputusan Pembelian dan Implikasinya pada Minat Beli Ulang - Popo Suryana; Eliyandi Sumar Dasuki (Faculty of Economics and Business, University of Pasundan, 2013)
This study aims to obtain empirical evidence about the “Effect of Service Quality and Store Image Purchase Decision And Implications On Repurchase Intention (A Survey On Consumer Motorcycles JG Motor Group in Bandung Region)”. In addition, this study wanted to know how the quality of service, store image, and Yamaha Motorcycles purchasing decisions are the implications on repurchase intention JG Motor Group in Bandung region. The method used was a survey method with a descriptive and explanatory approach. Data collection using questionnaires to a sample of 200 customers. Analysis of data analysis using SEM (Structural Equation Modeling). The results showed that the quality of service, store image was rated by the majority of consumers are already good, so is the customer purchase decision and repurchase intention. Service quality and store image influences purchase decisions either simultaneously or partially, as well as influencing purchase decisions of consumers repurchase intention JG Motor Group in Bandung region.